Modelling the long-term epidemiological and cost impact of a multicomponent lifestyle intervention and a sugar-sweetened beverage tax in the European Union: results from the EConDA project. (November 2016) - Pimpin, Laura; Perez-Ferrer, Carolina; Knuchel-Takano, Andre; Retat, Lise; Jaccard, Abbygail; Brown, Martin; Webber, Laura
Abstract: Background: Information on the efficacy and costs associated with targeting obesity can inform implementation of cost-effective policies. Within the Economics of Chronic Diseases (EConDA) project, we aimed to quantify the health and economic impact of two approaches to reduce chronic disease in eight European countries through to 2050: a multicomponent lifestyle intervention (MCLI) and a sugar-sweetened beverage tax. Methods: Body-mass index (BMI), disease epidemiology, and cost data for the diseases modelled (type 2 diabetes, coronary heart disease, stroke, and hypertension) were obtained from the literature for Bulgaria, Finland, Greece, Lithuania, the Netherlands, Poland, Portugal, and the UK. When country-specific data were not available, other countries were used as a proxy after adjustment for between-country differences. Mean change in BMI after annual MCLI to reduce energy intake and improve physical activity through behaviour change was obtained from the literature and was estimated after a 20% excise tax on sugar-sweetened beverages. A microsimulation model created country-representative synthetic populations. We determined simulated health outcomes in a baseline scenario using projections of BMI trends for each country up to 2050 and in two scenarios applying the interventions' respective BMI reduction to the BMI trends in the population. Simulated individuals developed diseases on the basis of their BMI and outputs provided the incidence and costs associated with the different scenarios. Findings: The prevalence of obesity and incidence of BMI-related disease was forecast to increase in all countries to 2050. MCLI had the largest effect on type 2 diabetes, ranging from 147 cases per 100 000 avoided (SD 17) in Bulgaria to 1003 (21) in Portugal by 2050. The highest costs avoided were for stroke (up to €1·15 million, SD €0·008 million) in Portugal. Although tax on sugar-sweetened beverages also had the largest effect on diabetes (from 5 per 100 000 cases avoided [SD 8] in the Netherlands to 87 [13] in the UK), the costs avoided were lower than for MCLI. Interpretation: These results highlight the variation in impact depending on the type of intervention aimed at the prevention of chronic diseases. An integrated approach to reducing obesity is required, so that a battery of approaches, varying in uptake and targeted population group, could be useful to obtain a greater effect on BMI reduction. Funding: European Commission Health Programme and the Executive Agency for Health and Consumers (project number 2012 12 13).